Abstracts of Oral and Poster Presentations: 25th Annual Academic Sessions of the College of Community Physicians of Sri Lanka - Ruwan Ferdinando; Ruwanika Seneviratne; Anoma Marasinghe; Niludi Yasaratna; Rimaza Niyas (College of Community Physicians of Sri Lanka, 2020)
NAA